Isokinetic muscle strength after anterior cruciate ligament reconstruction - Osteras, H.; Augestad, L. B.; Tondel, S. (Scandinavian Journal of Medicine & Science in Sports, 1998)
The purpose of the present study was to investigate the isokinetic muscle strength 6 months after reconstruction of the anterior cruciate ligament (ACL). In order to recommend full-load come-back in sport, sufficient muscle strength may be important. Ninety female elite team handball players (mean 24.1 years) were postoperatively tested with Biodex. The operated limb was compared with the contralateral limb: 82.2% had a hamstring strength of a minimum of 49.6 Nm, corresponding to at least 90% of the non-operated limb, while only 12.2% fulfilled the recommended strength of 117.7 Nm for quadriceps femoris. Patients over 26 years showed significantly lower muscle strength in the operated limb than their younger counterparts. Increased focus on quadriceps femoris muscle strength during rehabilitation may improve the knee function faster after ACL reconstruction. Scand J Med Sci Sports 1998 Oct;8(5 Pt 1):279-82